Medico-ethnobotany of Magar Community in Salija VDC of Parbat District, Central Nepal - Thapa, Shubhechchha (Our Nature, 2013)
This paper documents the ethno-medicinal use of plant species among the Magar community of Salija Village Development Committee from Parbat District in the central mid-hills of Nepal. The study recorded the use of 75 species of medicinal plants belonging to 46 families and 72 genera for the treatment of 39 different ailments. The most frequently treated illness were gastrointestinal ailments followed by dermatological infection and skeleto-muscular problem. Local healers and the knowledgeable groups were the one who mostly make use of medicinal plant species. The traditional home remedy is less practiced compared to the past years, and also lacks the sharing of knowledge among the practitioners. Documenting such herbal folklore knowledge is useful for further pharmaceutical research. DOI: http://dx.doi.org/10.3126/on.v10i1.7780